Perbandingan Aktivitas Belajar Siswa Yang Tinggal di Asrama dan di Luar Asrama Madrasah Aliyah Swasta (MAS) YASTI Singkawang Tahun 2019/2020 - Yusida Imran; Rima Maya Dela (Universitas Muhammadiyah Tangerang, 2021)
The results showed that the average learning activity of students living in dormitories was 98.35 with a percentage of 78% (high), with an average visual activities of 21.53 with a percentage of 86% (high), oral activitis of 19.48 with a percentage 77% (high), listening activities at 20.93 with a percentage of 83% (high), writing activities of 17.69 with a percentage of 70% (high), and mental activities of 18.69 with a percentage of 74% (high). While the average learning activity of students living outside the dormitory was 72.12 with a percentage of 57% (moderate), with an average visual activities of 16.21 with a percentage of 77% (high), oral activities of 13.53 with a percentage of 77% (high), oral activities of 13.53 with a percentage of 77% 64% (high), listening activities at 15.46 with a percentage of 73% (high), writing activities of 12.19 with a percentage of 58% (moderate), and mental activities of 14.95 with a percentage of 71% (high). Thus the average study activity of students living in dormitories was 98.35 with a percentage of 78% (high), and students living outside the dormitory at 72.12 with a percentage of 57% (moderate), with an average difference of 26,227 and a percentage difference of 21%. Hypothetical test results show a t count value greater than the table t (9,290 > 1,980). It can be concluded that there are significant differences in learning activities in Islamic Cultural History subjects between students living in dormitories and living outside the Private Madrasah Aliyah Dormitory (MAS) Yasti Singkawang in 2019/2020.